Tone and Threats on Television Over Time: A Longitudinal Analysis of News About Roma in Flanders - Jacobs, Laura (International journal of communication, 2020)
Anti-Roma prejudice is characterized as a unique form of prejudice because of its blatant nature. News about Roma has been overlooked as a key explanation for anti-Roma prejudice. This study aims to offer insight into news messages about Roma in a systematic and longitudinal way. To this end, I conducted a content analysis of 15 years of all television news stories (N = 181) about Roma in Flanders (2003–2017). Findings suggest a shift in patterns in news coverage of Roma. Although Roma are still underrepresented as a minority group on television and get a voice in only about one third of all news stories, uniformly negative news stories about Roma are on the decline in favor of more balanced news stories. Frames referring to blatant threats posed by Roma, such as criminal frames, are being replaced by more subtle frames. Journalists also more often portray Roma presence in society as a policy issue.